Quantitative information literacy: Designing an online course at the interface between information literacy and statistical literacy - Kläre, Christina (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2017)
Information literacy has become a large topic in libraries while statistical literacy is at most of secondary concern in library services. The article introduces the design of the online self-learning course “Daten und Statistiken recherchieren und nutzen” (“Searching and using data and statistics”) at the Duisburg-Essen University Library to show how an online course may fill the gap between reference services and courses about statistical methodology. With emphasis on the responsible librarians’ perspective and especially the didactical analysis and decisions, it is installed as numerical data service similar to subject guides. By using the learning management system Moodle, the course addresses students who study economics, political, or social sciences and plan to write an empirical paper. Während sich die Informationskompetenzunterstützung in unterschiedlichen Dienstleistungsausprägungen in Bibliotheken etabliert hat, spielt das Komplement Statistikkompetenz dort höchstens eine untergeordnete Rolle. Der Aufsatz erläutert die Erstellung des Online-Selbstlernkurses „Daten und Statistiken recherchieren und nutzen“ an der Universitätsbibliothek Duisburg-Essen und zeigt, wie ein solcher Onlinekurs eine Brücke zwischen den beiden Kompetenzen und insbesondere den Auskunftsdiensten der Bibliothek und der statistischen Methodenlehre schlagen kann. Der Aufsatz berücksichtigt vor allem die Anwendersicht unter Bezug auf die didaktischen Analysen und Entscheidungen beim Design des an Subject Guides/Forschungsführern orientierten Moodle-Kurses für die Zielgruppe Studierende der Wirtschafts-, Sozial- und Politikwissenschaften.